CYBER SECURITY DISCLOSURE: THE ROLE OF STAKEHOLDER PRESSURE AND GOVERNANCE QUALITY - Muhammad Fadhly Rizky Octavio; Noorfaiz Athallah Koeswandana (Faculty of Economics and Business University of Mataram, 2026)
This study explores how customer pressure, public digital pressure, and the quality of corporate governance influence cybersecurity disclosure in Indonesia’s banking sector. Using a quantitative panel data design, this study analyzed 115 observations by banks listed on the Indonesia Stock Exchange over 2020–2024. Cybersecurity disclosure was measured using word frequency analysis by Voyant Tools, while customer pressure was proxied by total customer deposits, public digital pressure by Google Trends scores, and corporate governance quality by the LSEG Management Score. Panel data regression by robustness checks through lagged regression and Propensity Score Matching were employed. Outcomes confirm that CP, PDP, and CGS each positively and significantly influence CSD. Differences in disclosure among state-owned and non-state-owned banks were also identified. Overall, the outcomes extend legitimacy theory to cybersecurity disclosure in emerging-market banking and support the use of Google Trends as a practical proxy for public digital pressure.